2023
DOI: 10.4317/jced.60452
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different adhesion strategies on glass fiber post retention

A. Nadler,
E. da Silva,
P. Lins-Filho
et al.

Abstract: Background Failures in glass fiber post (GFP) retention may be associated with low adhesion achieved in root dentin. Material and Methods 55 single-rooted premolars were endodontically treated and distributed according to different adhesion strategies (n=11): G1: RelyX ARC (3M ESPE; etch-rinse strategy); G2: Relyx Ultimate (3M ESPE; etch-rinse strategy); G3: AllCem (FGM; etch-rinse strategy); G4: Relyx Ultimate (3M ESPE; self-etching strategy); G5: RelyX U200 (3M ESPE; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…However, in the middle and the apical third, the group with the conventional resin cement combined with an etch-and-rinse adhesive system showed similar results to the group with the conventional resin cement combined with the self-etch adhesive system and the group with the self-adhesive resin cement. Scanning electron microscopy showed that conventional resin cements combined with etch-and-rinse adhesive systems created a more uniform hybrid layer with a greater number of resin tags compared to the hybrid layer created by the conventional resin cement combined with the self-etch adhesive system or the self-adhesive resin cement [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, in the middle and the apical third, the group with the conventional resin cement combined with an etch-and-rinse adhesive system showed similar results to the group with the conventional resin cement combined with the self-etch adhesive system and the group with the self-adhesive resin cement. Scanning electron microscopy showed that conventional resin cements combined with etch-and-rinse adhesive systems created a more uniform hybrid layer with a greater number of resin tags compared to the hybrid layer created by the conventional resin cement combined with the self-etch adhesive system or the self-adhesive resin cement [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…This acid removes the inorganic tissue inside and around the tubules, especially in the tubules perpendicular to the dentin surface [ 51 ]. The lengths of these tags range from 10 to 25 µm, except in those treated with universal adhesive, which show shorter length, lower density, and a thinner hybrid layer [ 52 ]. However, the resistance levels were similar, possibly due to the chemical binding of the MDP monomer to the residual hydroxyapatite linked to collagen fibers and the low solubility of the formed calcium salt [ 7 , 9 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…This acid removes the inorganic tissue inside and around the tubules, especially in the tubules perpendicular to the dentin surface [51]. The length of these tags ranges from 10 to 25 µm, except in those treated with Universal adhesive, which show shorter length, lower density, and a thinner hybrid layer [52]. However, the resistance levels are similar, possibly due to the chemical binding of the MDP monomer to the residual hydroxyapatite linked to collagen fibers and the low solubility of the formed calcium salt [7,9,[52][53][54][55][56][57][58][59][60][61][62].…”
Section: Discussionmentioning
confidence: 99%